Penentuan Cut-off Indeks Diskriminasi Diagnosis Pada Anemia Defisiensi Besi Dan Beta Thalassemia Minor - Bahraen, Raehanul (Jurnal Kedokteran, 2021)
Background: Beta thalassemia minor and iron deficiency anemia were most common cases of mild hypochoromic microcytic anemia. The differential diagnosis between beta thalassemia minor and iron deficiency anemia was important to avoid unnecessary iron therapy and to avoid false beta thalassemia minor diagnosis. We need valid and easy formula to make differentiate between them. It can be applied by using the red blood cell index (RBC) in the basic hematology examination. Methods: This study was a cross-sectional study with 30 samples of ADB and 30 samples of BTM in DR. Sarjito Hospital, Yogyakarta. Iron deficiency anemia was defined as microcytic anemia with mean corpuscular volume (MCV) <80 fL with ferritin levels <12 ?g / dl and hemoglobin A2> 3.5%. Beta thalassemia minor was defined as microcytosis with hemoglobin A2 ? 3.5%. We compared ten different discrimination formulas with seven red cell parameters. The calculation includes the cut-off value, sensitivity, specificity, positive predictive value , negative predictive value, and evaluation of the receiver operative characteristic (ROC) curve. Results: This study showed that Green & King, RDW index and Sirdah formula have the largest area under curve with value respectively 0.995; 0.992 and 0.0909 dan cut-off value <84.7; <240,7 and <40,12. Conclusion: The Green & King, RDW index and Sirdah formila were the highest formula to differentiate Beta thalassemia minor and iron deficiency anemia in DR. Sardjito hospital, Yogyakarta.